A Pragmatic Evaluation Of Directive Acts In Grade 10 English Textbook Instructions - Giselia Fatima Nurhaliza; Amir Hamzah; Lucky Rahayu Nurjamin (EDUJAVARE: International Journal of Educational Research, 2026)
This study examines how directive speech acts are realized in the written task instructions of an official Grade 10 EFL textbook used in Indonesia under the Kurikulum Merdeka. Textbook instructions function as primary written input that guides autonomous learner behavior, so their pragmatic formulation is important for preventing communication breakdowns. Grounded in Searle’s (1979) speech act taxonomy, this qualitative content analysis investigates the frequency distribution of directive forms across all chapters of the textbook. The results show a strong dominance of direct commands (72.73%), with requests (15.58%), suggestions (9.74%), and invitations (1.95%) appearing much less frequently. While direct imperative verbs contribute to task clarity and support independent learning, an overreliance on unmitigated commands diminishes the social complexity of the target language. This imbalance limits secondary level learners’ exposure to a range of polite and context-sensitive pragmatic structures that are crucial for real world English use. The study therefore recommends that textbook authors deliberately diversify task delivery formats to foster more balanced communicative competence among adolescent learners.